The examination and prediction of opencast backfill settlement - Hills, Christopher William Walter (1994)
With ever increasing demands on land use large areas of land are being considered for development which due to past or present mining activities are covered by substantial depths of fill materials. The problem faced with the development of land infilled with open cast mining backfill is in predicting the behaviour of the fill upon development. To be able to design foundations suitable to withstand the movements that occur within opencast backfill or design a backfilling operation that produces land suitable for a proposed after development, a means of predicting backfill settlement is required.